Workload Indicator Staffing Need (WISN) as A Method for Analyzing Clinic Health Personnel Needs in Surakarta - Asri Alfajri; Mazaya Bilqis Deswynand Sutedjo; Aswa Arsa Kumala (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Health Human Resources (HR) has an important role in providing health services to the community. HR management has a positive effect on organizational performance. Lack of health human resources is an important obstacle in achieving the highest level of health and as a result will limit opportunities to achieve comprehensive health goals. Health workforce planning is an important element in health service planning in building a responsive and efficient health service system. The use of workforce planning methods can contribute to the analysis and decision-making process for allocating the right number of professionals. WISN as a workload-based method can provide more accurate staff needs. This method has been used in various countries and has proven its significance in policy making regarding recruitment, distribution, training and reduction of human resources. Objective: This research aims to analyze the need for health workers at the Surakarta City Clinic using the WISN method. Method: This type of research is descriptive qualitative using interview methods with respondents and observation. The research was conducted at the 'Aisyiyah Medical Center Surakarta Clinic. The data was processed using qualitative data analysis and simple statistical techniques. Result: The research results showed that the need for health workers at the AMC Clinic based on the WISN method was 1 Dentist, 2 General Practitioners, 2 Nurses, 2 Midwives and 1 Pharmacy Personnel, this shows that the Clinic has an excess number of General Practitioner health workers but a shortage of Nurses. Conclusion: The workload of General Practitioners and Dentists is low, the workload of Midwives and Pharmacy Personnel is normal, and the workload of Nurses is high.